Tingkat Kelelahan Pada Pasen Gagal Ginjal Kronis Di Ruang Hemodialisa - Anggita, Kheniva Diah; Yoselina, Prima; Yuderna, Vivi (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Chronic kidney failure is a condition where kidney function decreases gradually due to kidney damage. One of the treatments that can be done to minimize the risk of causing further kidney damage is hemodialysis. Fatigue is the main complaint often experienced by chronic kidney failure patients undergoing long-term hemodialysis so that it will affect their quality of life. Purpose of the study: to determine the level of fatigue in chronic kidney failure patients undergoing hemodialysis. Method: cross sectional. Data Source: primary data in the form of observation sheets and secondary data in the form of a list of names of chronic kidney failure patients and supporting data obtained from room nurses. Research Results: The level of fatigue was generally at a moderate level in 17 people (56.7%) in chronic kidney failure patients in the hemodialysis room at Dr M Djamil Padang General Hospital, it is hoped that health services, especially nurses, can identify and overcome the level of fatigue in chronic kidney failure patients undergoing hemodialysis.